BRONCHOPULMONARY DYSPLASIA IN PRETERM CHILDREN: PATHOMORPHOLOGICAL FEATURES OF DEVELOPMENT - Bykovska, O.A.; Yablon, O.S.; Savrun, T.I.; Procuіk, T.L.; Kyslova, Yu.O. (World of Medicine and Biology, 2018)
The article presents the results of pathomorphological research of pulmonary tissue in 19 deep premature newborns born with a birthweight less than 1500 grams, gestational age less than 32 weeks and the risk factors of forming of Bronchopulmonary Dysplasia has been performed, using histological and immunohistochemical methods. The purpose of our work was to study the pathomorphological and immunohistochemical features of pulmonary tissue in the formation of a "new" form of bronchopulmonary dysplasia in extremely preterm infants. Depending on the life expectancy of the deceased, the children were divided into 3 groups:Group 1 - 5 deeply premature babies who died in the early neonatal period (up to 7 days of life).Group 2 - 10 deeply premature babies who died in the late neonatal period (from 7 to 28 days of life inclusive).Group 3 - 4 children who died at the age from 30 days to 4.5 months.Histological examination of pulmonary tissue in children of group 1 revealed changes characteristic of bronchopneumonia with acute inflammatory exudate in the lumen of immature alveoli, macrophage reactions and desquamation of the epithelium. Histological examination of the pulmonary tissue in children of the 2nd group demonstrated the presence of hemorrhages in the respiratory unit of the bronchi, foci of atelectasis and areas of emphysematous enlarged immature alveoli in 100% of cases.Simultaneously with the above-mentioned changes, there were foci of vascular malformations and vascular angiodysplasia. In deeply mature children, in the histological examination of pulmonary tissue in group 3, in all cases of observation common centers of respiratory bronchioles atelectasis have been revealed, which in the literature is called "murary atelectasis". In addition, in children of group 3, bronchioles with hyperplasia and prolapse of the mucous membrane were histologically revealed, which led to thickening of the bronchioles wall and narrowing or even closing their lumen. Consequently, the histological and immunohistochemical study of pulmonary tissue in deeply preterm infants with risk factors for BPD, revealed damage to respiratory, bronchoalveolar and vascular segments.In all study groups, morphological vascular changes can be characterized as angiodysplasia, in the form of the presence of immature vessels with severe malformation, thickening of the wall and general violations of architectonics, were revealed. Immunohistochemical changes of the respiratory, bronchoalveolar and vascular branches of the pulmonary tissue were also revealed as accumulation of Vimentine in the vessels wall of the immature alveoli and bronchioles. In addition, there was a low level of nuclear antigen expression in the areas of pulmonary dysplasia and vascular malformations. The obtained results indicate the decrease regenerative capacity of the pulmonary tissue in the late neonatal period, the absence of the pulmonary tissue regeneration processes in the postneonatal period and, accordingly, the interruption of the alveolarization and angiogenesis
Keywords: preterm newborn; Bronchopulmonary Dysplasia; proliferative cell nuclear antigen; mesenchimal factor Vimentin